Trade in Counterfeit Goods in Serbia – Methodological Approach and Quantification - Radulovic, Branko (Industrija, 2021)
The paper represents the first step in quantifying the categories of goods with the highest risk of being counterfeit during import into Serbia. Firstly, we present a methodology for quantifying the level of counterfeiting, its advantages, and its limitations. Secondly, we determine the product categories most likely to contain counterfeit products. Likewise, by using the OECD methodology, the GTRIC-p indicator for Serbia was formed, which enables comparison with OECD member countries. Based on the results, Serbia does not significantly differ from EU countries in terms of structure and product categories most at risk. The negative effects of imports of counterfeit products are borne mainly by the foreign IPR holders whose counterfeit products are imported into Serbia. In this context, despite the legal framework in place, incentives for its proper implementation are questionable.